Interaction of magnetic reconnection and Kelvin‐Helmholtz modes for large magnetic shear: 2. Reconnection trigger. Issue 2 (3rd February 2014) - Ma, Xuanye; Otto, Antonius; Delamere, Peter A.
<x xml:space="preserve">Abstract</x> A typical property of magnetopause reconnection is a significant perpendicular shear flow due to the fast streaming magnetosheath plasma. Therefore, the magnetopause represents a large magnetic and flow shear boundary during periods of southward interplanetary magnetic field, which can be unstable to Kelvin‐Helmholtz (KH) modes and to magnetic reconnection. A series of local three‐dimensional MHD and Hall MHD simulations is carried out to investigate the interaction of reconnection and nonlinear KH waves considering magnetic reconnection as the primary process. It is demonstrated that the onset reconnection causes a thinning of the shear flow layer, thereby generating small wavelength KH modes. In turn, the growing KH modes modify the current layer width, which modulate the diffusion regions, increase the local reconnection rates, and generate field‐aligned currents. The simulation results imply a limitation of total amount of open flux likely caused by nonlinear saturation of KH growth and the associated diffusion. It is also demonstrated that the reconnection rate maximizes for conditions that allow a strong nonlinear evolution of KH waves, i.e., fast shear flow and limited guide magnetic field. The presence of Hall physics increases the reconnection rate in the early stage; however, the maximum reconnection rate and the total amount of open flux at saturation are the same as in the MHD case.